Funcionalidad de la mano luego de una carpectomía proximal: primer caso en el servicio de kinesiología de la Universidad Nacional de Asunción - Ibañez, Lenis; Bernaola, Claudia; Cuevas, Silvia; Almirón, Marcos (Medicina Clínica y Social, 2024)
The wrist is the anatomical segment that allows the hand to be brought closer to the mouth. Fractures and dislocations of the carpal bones are rare, accounting for between 5-7% of fractures of the wrist and hand, and occur through high-risk trauma. energy thus generating a significant physical and functional disability for the patient. Proximal row carpectomy aims to preserve the mobility of the wrist and reduce its impairment for activities of daily living. We present a 41-year-old male patient with a sawmill profession who was referred to physiotherapy rehabilitation after surgery due to high-energy trauma to the dominant hand through a traffic accident. The evolution was favorable, after 8 weeks of physiotherapy rehabilitation and following an intervention protocol mediated by therapeutic and rehabilitation exercises, the patient was able to perform voluntary activities with the hand related to mobility and grip strength.